Following Method (Rothkopf) to acquire Islamic concepts in Islamic Education's average second grade students. (Journal of the College of Basic Education, 2022)
The collection of values is not effective for them did not turn to the behavior and work and practice-oriented, and this should ensure that teachers ensure that these values are concrete with students before they are mere subjects included in the curriculum.The higher the educational goals set by the teacher and clear for both the teacher and the student, the more optional method was the most successful and luckier than other methods. Nominal final of the educational process is to build knowledge and acquisition of skills and development tendencies and positive attitudes towards the material.The foregoing reflects the research problem that there is an urgent need to conduct such a study and the need to know the effect of the method (Rothkopf) to acquire Islamic concepts in Islamic Education's average second grade students.